Québec Incidence Study on the situations investigated by child protective services: Major findings for 2008 and comparison with 1998 - Hélie, Sonia (Can J Public Health, 2015)
OBJECTIVE: The Québec Incidence Study on situations investigated by child protective services (QIS) has been conducted in 5-year cycles since 1998 in collaboration with all 16 Québec child protection agencies. It provides reliable estimates of the incidence and characteristics of investigated children. The aim of this paper is to discuss major findings from the QIS-2008 and to compare them with the findings from QIS-1998. METHODS: Two representative samples of children who were investigated by child protection services during the same three-month time frame in 1998 (N = 4,771) and in 2008 (N = 3,079) were constituted. Caseworkers were asked to complete the QIS data collection form for each sampled child. Annual estimates of the number of children investigated with different characteristics were computed and compared across both cycles. Statistical tests were performed to identify significant differences. RESULTS: While the rate of children investigated increased between 1998 and 2008, the rate of substantiated cases remained stable at 12 and 11 per 1,000 children in the population respectively. Furthermore, substantiated cases in 2008 were less severe than in 1998 along several dimensions, such as co-occurrence, emotional harm and duration. CONCLUSION: Combined with the stability in the rate of substantiated cases, the decline in the severity of the situations seems encouraging but questions the necessity of a CPS intervention for some of these families. These findings are consistent with the ones reported in other countries, but Québec rates are below the rates estimated for Canada, where substantiated maltreatment almost doubled during the same time frame. Aspects of social policies in Québec may play a role in this situation and need to be examined in future research.